Application of endoport-assisted neuroendoscopic techniques in lateral ventricular tumor surgery - Yan, Chaolong; Mao, Jiannan; Yao, Chenbei; Liu, Yang; Jin, Wei; Yan, Huiying (Frontiers in Oncology, 2023)
Objective The objective of this study was to investigate the clinical experience and therapeutic efficiency of Endoport-assisted neuroendoscopic surgery for resection of lateral ventricular tumors. The key points and application value of this surgical technique were additionally discussed. Methods A retrospective analysis was conducted on the clinical and follow-up data of 16 patients who underwent endoport-assisted neuroendoscopic surgery for lateral ventricular tumors at the Department of Neurosurgery, Nanjing Drum Tower Hospital, the Affiliated Hospital of Nanjing University Medical School, between January 2018 and September 2020. The surgical procedures, complications and outcomes were analyzed. Results The study included a total of 16 patients (5 males and 11 females) with lateral ventricular tumors, with a mean age of 43.2 years (18-70 years old). The tumors were distributed as follows: 5 cases involved the body of the lateral ventricle, 3 involved the frontal horn and body, 3 involved the occipital horn, 2 involved the trigone, 2 involved the frontal horn, and 1 case involved the occipital horn and body. Perioperative complications were analyzed, revealing 1 case of intraoperative acute epidural hematoma intraoperative and 2 cases of postoperative obstructive hydrocephalus. All complications were promptly managed. Postoperative MRI revealed that 14 cases (88%) achieved total resection, while 2 cases (12%) achieved subtotal resection. During the follow-up of 6-38 months, no recurrence was observed. The patient diagnosed with glioblastoma died 16 months after surgery (GOS=1), while the remaining patients have successfully resumed to normal daily life with a GOS score of 5. Conclusion In conclusion, endoport-assisted neuroendoscopic surgery proved to be a minimally invasive and effective technique for resecting lateral ventricular tumors, with acceptable complications. It effectively utilizes the benefits of close observation, comprehensive exposure, and reduced tissue damage. Therefore, endoport-assisted neuroendoscopic surgery is suitable for the resection of lateral ventricular tumors.